Building national identity through the secondary school literature component in Malaysia / Raphael Thoo Yi Xian, Foong Soon Seng, Khor Zyeh Lyn and Pong Kok Shiong - Yi Xian, Raphael Thoo; Soon Seng, Foong; Zyeh Lyn, Khor; Kok Shiong, Pong (Universiti Teknologi MARA, Kedah, 2017)
This study seeks to analyze the themes prevalent in the Form 1-3 literary texts since the reintroduction of the literature component into Malaysia’s secondary school curricula in 2000, up to the most recent Kurikulum Standard Sekolah Menengah (KSSM) which is to be implemented in 2017. According to the National Education Blueprint (2013-2025), national identity is one of the six student aspirations. The incorporation of this theme would aid students to better understand their multiethnic culture and build their national identity (Kaur and Mahmor, 2014); this paper employed thematic analysis to further investigate the prevalence of the theme of nationhood in these texts. Findings show that only one text hinted the theme of nationhood out of 10. Other foreign texts contained a variety of themes other than that of nationhood. Past studies indicated that the literary texts should have a balance of local and foreign texts. Local works should be introduced first, especially in the lower secondary level (Ghazali, Setia, Muthusamy, and Jusoff, 2009; Isa and Mahmud, 2012; Kaur and Mahmor, 2014). However, the current literary texts in the KSSM do not correlate with the aspiration in the National Education Blueprint.